SECURITY EVALUATION ON THE STEEL STRUCTURE OF LIFT-SLIDING STEREO GARAGE - CHEN HongYan; WANG JianBo; LIU Peng; GUO DongJun (Jixie qiangdu)
The statics and dynamics analyses for the steel structure of a type of single-row, three-column, five-layer lift-sliding stereo garage were carried out based on the ANSYS software and the finite element modeling. Analyses proved the safety reliability of steel structure under the extreme conditions, and the weak points of steel structure were found out. The strain monitoring program at these weak positions was designed and finished. The results of analysis were substantial agreement with the experimental results. The maintenance and design personnel could also carry on the security evaluation to the steel structure of the stereo garage through the strain monitoring data, formulate the reasonable maintenance plan, optimize the design of the structure, and improve the service life of the equipment.